Path planning algorithm for a car-like robot based on cell decomposition method - Omar, Nurhanum (2013)
This project proposes an obstacle avoiding path planning algorithm based on cell decomposition method for a car-like robot. Dijkstra’s algorithm is applied in order to find the shortest path. Using cell decomposition, the free space of the robot is exactly partitioned into cells. Then, the connectivity graph is created followed by calculating the shortest path by Dijkstra’s algorithm. This project also concerns the robot kinematic constraints such as minimum turning radius. Thus, kinematic modeling and Bezier curve have been used to obtain a feasible path. The algorithm is able to obtain a curvature bounded path with sub-optimal curve length while taking cell decomposition as reference skeleton. The C-space concept has been applied in this situation. The obstacles on the map are expanded according to the size of car-like robot, so that the robot could be treated as points on this map and the coordinates of the map is corresponding to these points. The simulation and experimental result shows the algorithm can obtain the collision free path which satisfies the curvature constraint and approaches the minimal curve length for a car-like robot.